Investigation of the Incidence of Coital Incontinence in Incontinent Women - Demir, Omer; Comba, Cihan (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: Coital incontinence is the involuntary leakage of urine during sexual intercourse and is rarely reported in women with urinary incontinence. The aim of this study is to investigate the frequency of coital incontinence and its association with incontinence types. Study Design: All sexually active women with urinary incontinence (diagnosed as self-reported) attending the out-patient gynecology clinic of a regional state hospital were interviewed consecutively between September 2017 and September 2018 about their experience with regards to coital incontinence. The clinical evaluation consisted of medical history, physical examination, and urine analysis. The SPSS 20 program designed for Windows was used for statistical analysis. Results: Twenty-two of the 64 women who participated in the study were diagnosed with coital incontinence and the remaining 42 women were to be compared. 42 women were included in the control group, and 22 women were defined as the study group. The women with coital incontinence had significantly higher stress test positivity than the control group (p = 0.00). No significant differences in the frequency of coital incontinence between incontinence types were found. The chi-square test was applied, and the p-value was >0.05 (p=0.110). So there was no statistically significant relationship between the type of incontinence and the frequency of coital incontinence. Conclusion: Coital incontinence is much more prevalent than expected and therefore patients with symptomatic urinary incontinence should be investigated for the presence of coital incontinence, as this may affect patient approach and treatment.